Relationship between stock market and macroeconomic variables / Syazwani Ezzaty Zafrin - Zafrin, Syazwani Ezzaty (Faculty of Business Management, 2015)
The aim of this study is to investigate the relationship between Exchange Rate, Inflation Rate, Money Supply, and Interest Rate to the Stock Market Indices. The study used Simple Linear Regression and Multiple Linear Regression in order to find the relationship among those indices. The quarterly closing data were collected from January 2006 until January 2015. From the result, it reveals that certain variables have a significant negative relationship towards Stock Market Indices and the others are insignificant. It means that there are macroeconomic variables that interdependence towards the Stock Market Indices. Based on the results, it shows further understanding of the relationship between the macroeconomic variables to the Stock Market Indices and it may be useful for regulators, investors, and speculators.